Retrospective study of commercial poultry diseases - Ausraful Islam; Shankar Majumder; Asadur Rahman; Ashika Akbar Trisha; Ruhul Amin (Eurasian Journal of Veterinary Sciences)
The aim of this study was to explore the occurrence of different diseases among commercial chickens. A total of 232 commercial chickens were divided into different age groups and the whole year was divided into three seasons. The occurrence of parasitic diseases was the highest among layers (81.9%) and broilers (95.2%). Occurrence of bacterial diseases (p<0.01) and parasitic diseases (p<0.05) was significantly lower in summer than rainy and winter seasons. Viral diseases were observed among 25.2% layers and occurrence was significantly (p<0.01) higher in pullet stage (40.9%) compared to laying stage (8.2%). Occurrence of non-infectious (p<0.01) disease, cannibalism (p<0.05) and egg bound disease (p<0.05) was significantly higher in laying stage compared to pullet stage. Bacterial disease occurrence was significantly (p<0.01) lower in 8-21 days age group compared to 0-7 days age group of broilers. Occurrence of viral diseases was significantly (p<0.01) higher among broilers of 22-35 days age group compared to 0-7 days age group. Several infectious and noninfectious diseases are prevalent among the commercial poultry of Guibandha district which can be controlled by effective vaccination and good management practices.